REPRESENTASI FEMINISME DAN PEMBERDAYAAN PEREMPUAN DI PULAU AMAZON LILY DALAM SERIAL ANIME ONE PIECE - Arif Sugitanata; Siti Aminah; Muhammad Hasyied Abdurrasyied (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2024)
This research examines the representation of feminism and women's empowerment in "One Piece," specifically on Amazon Lily Island, as depicted in episodes 408 to 421 of the anime series. This study employs a literature review and a qualitative research approach with a descriptive-analytical method to investigate how Amazon Lily Island, as a matriarchal society, embodies feminist values through the independence, strength, and solidarity of its women. Unlike previous studies focusing on feminist characters in films and television series, this research emphasizes the distinctiveness of Amazon Lily Island in the "One Piece" narrative, reflecting key themes such as gender, power, and matriarchy. The findings reveal that the island's female characters, especially Queen Boa Hancock, epitomize strong and autonomous female archetypes yet grapple with the paradox of power and vulnerability. This study enriches the literature on feminism in media, particularly in anime, and discusses how the Amazon Lily Island narrative contributes to a broader understanding of women's empowerment and the challenges they encounter in a patriarchal society.